Pengaruh Inflasi, Suku Bunga dan Kurs Terhadap Indeks Harga Saham Gabungan (IHSG) Pada Perusahaan yang terdaftar di BEI - Susilo Adi; Rachmat Setyawan; Robby Andika Kusumajaya (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Main Problem: Differences in previous research on the influence of inflation, interest rates and exchange rates on the IHSG value. Purpose: to carry out a form of test and analyze inflation against the IHSG. Apart from that, it will also be analyzed how interest rates affect the JCI. Then it will also be analyzed how the exchange rate influences the JCI. Originality: This research focuses on conducting tests and analyzing inflation, interest rates and exchange rates in influencing the IHSG. Method: This research falls into the category of quantitative research. This research was carried out as a case study to provide a detailed, in-depth and comprehensive explanation of objects in a limited area. Results: Based on the results after testing the analysis system with a multiple linear regression model and by carrying out a t test, this way we can we conclude that a value of inflation and a value of interest rates have a negative influence on the value of the IHSG (composite stock price index), but meanwhile the value of an exchange rate has a positive influence on the IHSG ( composite stock price index).